Hubungan Kekerasan Verbal Dalam Berkomunikasi Orangtua Kepada Anak Terhadap Status Kesehatan Mental Emosional Anak Usia Prasekolah - Diva Adesyahpuri; Syeptri Agiani Putri; Ririn Muthia Zukhra (Universitas Malahayati Lampung, 2026)
ABSTRACT The childhood stage is the most important stage in human development. The psychosocial development of preschool children is initiative and feelings of guilt. However, some parents have problems with their children using verbal violence in communicating. This causes children to become aggressive, withdraw from the environment, and can hinder learning at home and school. This research uses a descriptive correlation design with a cross sectional approach. The sample consisted of 100 parents, with sampling using a stratified random sampling technique. The analysis of this research consists of univariate using descriptive tests and bivariate using chi-square tests. The majority of respondents who used verbal violence in communicating were in the low category, amounting to 80 people (80%). The emotional mental health status of preschool age children is dominated by normal, numbering 75 people (75%). Respondents who used verbal violence in communicating were in the high-medium category with the emotional mental health status of normal and troubled preschool age children totaling 12 people (100%), while respondents who used verbal violence in communicating with children were dominated by the low none category with the emotional mental health status of normal preschool age children was 69 people (78.4%). Therefore, the statistical test results obtained a p value (0.068) α (0.05). This research shows that there is no relationship between verbal violence in parent-to-child communication and the mental-emotional health status of preschool-age children. It is hoped that health workers will carry out early detection using verbal violence questionnaires in parental communication and KMME in preschool children. Keywords: Preschool Aged Children, Verbal Violence, Parental Communication, Emotional Mental Health Status. ABSTRAK Tahap anak merupakan tahapan terpenting pada perkembangan manusia. Perkembangan psikososial anak usia prasekolah adalah inisiatif dan perasaan bersalah. Namun, beberapa masalah orangtua kepada anak ada yang menggunakan kekerasan verbal dalam berkomunikasi. Hal ini menyebabkan anak menjadi agresif, menarik diri dari lingkungan, serta dapat menghambat belajar di rumah dan sekolah. Penelitian ini menggunakan desain deskriptif korelasi dengan pendekatan cross sectional. Sampel berupa orangtua sebanyak 100 orang, dengan pengambilan sampel menggunakan teknik stratified random sampling. Analisis penelitian ini, terdiri dari univariat menggunakan uji deskriptif dan bivariat dengan uji chi-square. Mayoritas responden yang menggunakan kekerasan verbal dalam berkomunikasi pada kategori rendah berjumlah 80 orang (80%). Status kesehatan mental emosional anak usia prasekolah didominasikan oleh normal berjumlah 75 orang (75%). Responden yang menggunakan kekerasan verbal dalam berkomunikasi pada kategori tinggi sedang dengan status kesehatan mental emosional anak usia prasekolah yang normal dan bernasalah berjumlah 12 orang (100%), sedangkan responden yang menggunakan kekerasan verbal dalam berkomunikasi kepada anak didominasikan oleh kategori rendah-tidak ada dengan status kesehatan mental emosional anak usia prasekolah yang normal berjumlah 69 orang (78,4%). Maka dari itu, hasil uji statistik diperoleh nilai p value (0,068) α (0,05). Penelitian ini menunjukkan tidak ada hubungan kekerasan verbal dalam berkomunikasi orangtua kepada anak terhadap status kesehatan mental emosional anak usia prasekolah. Diharapkan bagi tenaga kesehatan untuk melakukan deteksi dini dengan kuesioner kekerasan verbal dalam berkomunikasi orangtua dan KMME pada anak usia prasekolah. Kata Kunci: Anak Usia Prasekolah, Kekerasan Verbal, Komunikasi Orangtua, Status Kesehatan Mental Emosional.